2008
DOI: 10.4049/jimmunol.180.3.1895
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deimination As a Response to Inflammatory Stimuli in Neutrophils

Abstract: Posttranslational modifications, such as the deimination of arginine to citrulline by peptidyl arginine deiminase (PAD4), change protein structure and function. For autoantigens, covalent modifications represent a mechanism to sidestep tolerance and stimulate autoimmunity. To examine conditions leading to histone deimination in neutrophils, we used Abs that detect citrullines in the N terminus of histone H3. Deimination was investigated in human neutrophils and HL-60 cells differentiated into granulocytes. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
529
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 496 publications
(555 citation statements)
references
References 50 publications
22
529
2
2
Order By: Relevance
“…Citrullination of proteins causes a loss of positive charge and results in a significant biochemical effect. Bacterial infection has been indicated to stimulate PADI4-mediated hypercitrullination of histones in neutrophils and subsequently promoted highly decondensed extracellular chromatin structure called NET (neutrophil extracellular trap) that could capture and kill microorganisms 12,13 . On the other hand, citrullinated peptides/proteins are recognized as non-self proteins and subsequently activate immune systems.…”
mentioning
confidence: 99%
“…Citrullination of proteins causes a loss of positive charge and results in a significant biochemical effect. Bacterial infection has been indicated to stimulate PADI4-mediated hypercitrullination of histones in neutrophils and subsequently promoted highly decondensed extracellular chromatin structure called NET (neutrophil extracellular trap) that could capture and kill microorganisms 12,13 . On the other hand, citrullinated peptides/proteins are recognized as non-self proteins and subsequently activate immune systems.…”
mentioning
confidence: 99%
“…Thus, NETosis should be considered a distinct cell death program. It was recently shown that decondensation of nuclear chromatin preceding NET formation is mediated by histone citrullination [7,10]. The inability of CGD neutrophils to generate NETs in response to PMA indicates that Nox2 activity is essential for the intracellular chromatin decondensation that precedes NET formation [6], but this was not demonstrated directly.…”
Section: Discussionmentioning
confidence: 96%
“…These vesicles have a double phospholipid bilayer and are believed to originate from the nuclear envelope [6,9], which disintegrates during NET cell death. Finally, but still before plasma membrane permeabilization, nuclear chromatin decondenses and mixes with the contents of the granules; this is essential for formation of functional NETs [7,10]. Permeabilization of the neutrophil plasma membrane releases these chromatin structures, which are loaded with concentrated antimicrobial molecules, such as lactoferrin, BPI, LL-37 and histones [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, NF-kB was also reported to be regulated by other PRMTs (48)(49)(50), suggesting that arginine methylation plays unique roles in NF-kB activation. In addition, it has been reported that histone arginine deimination, which antagonizes arginine methylation, is a response to a wide range of inflammatory stimuli (51,52). Thus, we speculate that PRMT7-mediated arginine methylation may be able to regulate genes involved in mammalian immune and inflammatory responses, and the deletion of PRMT7 in B cells might impair B cells and induce an immune deregulation reminiscent of sterile inflammation.…”
Section: Discussionmentioning
confidence: 99%